Phase II clinical trial using anti-CD3 × anti-HER2 bispecific antibody armed activated T cells (HER2 BATs) consolidation therapy for HER2 negative (0–2+) metastatic breast cancer. Issue 6 (11th June 2021) - Lum, Lawrence G.; Al-Kadhimi, Zaid; Deol, Abhinav; Kondadasula, Vidya; Schalk, Dana; Tomashewski, Elyse; Steele, Patricia; Fields, Kristie; Giroux, Melissa; Liu, Qin; Flaherty, Lawrence; Simon, Michael; et al.
Abstract : Background: Metastatic human epidermal growth receptor II (HER2) negative breast cancer remains incurable. Our phase I study showed that anti-CD3 × anti-HER2 bispecific antibody armed activated T cells (HER2 BATs) may be effective against HER2-tumors. This phase II trial evaluates the efficacy and immune responses of HER2 BATs given to patients with metastatic HER2-estrogen and/or progesterone receptor positive (HR+) and triple negative breast cancer (TNBC) as immune consolidation after chemotherapy. The primary objective of this study was to increase the traditional median time to progression after failure of first-line therapy of 2–4 months with the secondary endpoints of increasing overall survival (OS) and immune responses. Methods: HER2- metastatic breast cancer (MBC) patients received 3 weekly infusions of HER2 BATs and a boost after 12 weeks. Results: This phase II study included 24 HER2-HR+ and 8 TNBC patients who received a mean of 3.75 and 2.4 lines of prior chemotherapy, respectively. Eight of 32 evaluable patients were stable at 4 months after the first infusion. There were no dose limiting toxicities. Tumor markers decreased in 13 of 23 (56.5%) patients who had tumor markers. The median OS was 13.1 (95% CI 8.6 to 17.4), 15.2 (95% CI 8.6 to 19.8), and 12.3 (95% CI 2.1 to 17.8) months for the entire group, HER2-HR+, and TNBC patients, respectively. Median OS for patients with chemotherapy-sensitive and chemotherapy-resistant disease after chemotherapy was 14.6 (9.6–21.8) and 8.6 (3.3–17.3) months, respectively. There were statistically significant increases in interferon-γ immunospots, Th1 cytokines, Th2 cytokines, and chemokines after HER2 BATs infusions. Conclusions: In heavily pretreated HER2-patients, immune consolidation with HER2 BATs after chemotherapy appears to increase the proportion of patients who were stable at 4 months and the median OS for both groups as well as increased adaptive and innate antitumor responses. Future studies combining HER2 BATs with checkpoint inhibitors or other immunomodulators may improve clinical outcomes.